2015
DOI: 10.1021/acsmedchemlett.5b00272
|View full text |Cite
|
Sign up to set email alerts
|

Novel Oxindole Sulfonamides and Sulfamides: EPZ031686, the First Orally Bioavailable Small Molecule SMYD3 Inhibitor

Abstract: SMYD3 has been implicated in a range of cancers; however, until now no potent selective small molecule inhibitors have been available for target validation studies. A novel oxindole series of SMYD3 inhibitors was identified through screening of the Epizyme proprietary histone methyltransferase-biased library. Potency optimization afforded two tool compounds, sulfonamide EPZ031686 and sulfamide EPZ030456, with cellular potency at a level sufficient to probe the in vitro biology of SMYD3 inhibition. EPZ031686 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 13 publications
2
84
1
Order By: Relevance
“…EPZ031686 is a noncompetitive inhibitor for SAM and the MAP3K2 substrate, while EPZ030456 showed mixed type inhibition with respect to SAM, and noncompetitive inhibition with respect to MAP3K2. EPZ031686 also displayed good bioavailability in mice, making it a suitable compound for in vivo studies [95].…”
Section: Design and Testing Of Smyd3 Inhibitorsmentioning
confidence: 99%
“…EPZ031686 is a noncompetitive inhibitor for SAM and the MAP3K2 substrate, while EPZ030456 showed mixed type inhibition with respect to SAM, and noncompetitive inhibition with respect to MAP3K2. EPZ031686 also displayed good bioavailability in mice, making it a suitable compound for in vivo studies [95].…”
Section: Design and Testing Of Smyd3 Inhibitorsmentioning
confidence: 99%
“…For example, the cocrystal structure of the substrate-competitive, SAM-uncompetitive SMYD2 inhibitor AZ505 in complex with SMYD2 and SAM, showed that the ketone oxygen of the benzooxazinone moiety is 2.8 Å away from the sulfonium methyl group, which can act as a hydrogen-bond donor [47,85]. Stabilizing amide-sulfonium interactions have also been reported for other SMYD-family inhibitors such as EPZ030456 and an AZ505-analog called A-893 [86,87].…”
Section: Setd7 Smyd2 and Suv420h1/2mentioning
confidence: 90%
“…The SMYD (SET and MYND domain‐containing) family proteins are also histone methyltransferases, and one of them, SMYD3, is H3 K4 methyltransferase. EPZ031686 was reported as an inhibitor of SMYD3 . SMYD2 was reported to methylate H3 K4 and H3 K36 as well as other substrates, such as tumor suppressor proteins p53 and Rb (retinoblastoma protein) .…”
Section: Inhibitors Of H3 K4 and H3 K36 Methylationmentioning
confidence: 99%